2021
DOI: 10.3390/ijms222011032
|View full text |Cite
|
Sign up to set email alerts
|

Mining Fiskeby III and Mandarin (Ottawa) Expression Profiles to Understand Iron Stress Tolerant Responses in Soybean

Abstract: The soybean (Glycine max L. merr) genotype Fiskeby III is highly resistant to a multitude of abiotic stresses, including iron deficiency, incurring only mild yield loss during stress conditions. Conversely, Mandarin (Ottawa) is highly susceptible to disease and suffers severe phenotypic damage and yield loss when exposed to abiotic stresses such as iron deficiency, a major challenge to soybean production in the northern Midwestern United States. Using RNA-seq, we characterize the transcriptional response to ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…Based on this, Glyma.06G115800 is likely to maintain Al balance by transporting Al into cells or out of cells. Previous research has demonstrated that Glyma.15G251300 encoding nicotianamine synthase NAS1 plays a central role in long-distance Fe transport [ 44 ]. Though Al transport was not involved in the research, other research has proved that mugineic acid (MA), with nicotianamine (NA) as the important intermediate in its production, has the ability to bind to Al [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, Glyma.06G115800 is likely to maintain Al balance by transporting Al into cells or out of cells. Previous research has demonstrated that Glyma.15G251300 encoding nicotianamine synthase NAS1 plays a central role in long-distance Fe transport [ 44 ]. Though Al transport was not involved in the research, other research has proved that mugineic acid (MA), with nicotianamine (NA) as the important intermediate in its production, has the ability to bind to Al [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…SPAD measurements have been used to map IDC QTLs and confirm the identification of IDC QTLs visual scores ( Lin et al., 1997 , Lin et al., 2000 ; Assefa et al., 2020 ). In addition, SPAD measurements have been used in IDC gene expression analyses ( O’Rourke et al., 2007 , O’Rourke et al., 2009 ; Atencio et al., 2021 ; Kohlhase et al., 2021 ) and to phenotype VIGS plants in terms of response to iron stress ( Atwood et al., 2014 ; O’Rourke et al., 2021 ). The average of six SPAD readings per trifoliolate, two readings per leaflet, was calculated for the first and second trifoliolates for eight plants per construct.…”
Section: Methodsmentioning
confidence: 99%
“…In soybean, researchers have adopted virus-induced gene silencing (VIGS) as a relatively fast and inexpensive tool that can target single genes or gene families ( Zhang and Ghabrial, 2006 ; Zhang et al., 2013 ). Targeted traits include resistance genes and defense gene networks ( Meyer et al., 2009 ; Liu et al., 2011 ; Pandey et al., 2011 ; Liu et al., 2012 ; Cooper et al., 2013 ; Kandoth et al., 2013 ; Morales et al., 2013 ; Xu et al., 2018 ; Pedley et al., 2019 ) and candidate abiotic stress genes ( Atwood et al., 2014 ; Sun et al., 2016 ; Ogata et al., 2017 ; O’Rourke et al., 2021 ; O’Rourke and Graham, 2022 ). Atwood et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations